LEADING THINKERS@USM SHARE THEIR EXPERIENCE WITH JKPU MEMBERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PETALING JAYA, April 2015 Leading Thinkers, a group consisting of six experts and businessmen based locally and abroad shared their experience and expertise with the members of the Universiti Sains Malaysia (USM) University Management Committee (JKPU) here recently.